IMAGE RECOGNITION IN THE TRAFFIC SIGN SYSTEM - SEMIOTIC AND LINGUISTIC ASPECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The traffic sign system is a complex structure composed of images and verbal text. This research aims to focus on the nature of the road sign as an image, its recognition by road users, the relationship between verbal text and image in road sign design, how much they interact and how text contributes to the basic functions of the sign - to direct and regulate traffic and the behaviour of road users. The theory of sign, a subject of study in semiotic science, is examined. The sign as an image influences, informs, regulates the behaviour of road users - these are its main functions. The system of road signs is composed on the basis of a common code of symbols and images, which is modified in different linguistic and cultural environments. The text component complements and supports the functions of the image. Its structure and pattern in different languages are also investigated in order to check the necessity or redundancy of the verbal text in the composition of the road sign as a whole. By using an interdisciplinary approach between semiotics and linguistics, the research could be extended towards improving the design of road signs in order to improve communication on the road through the road sign system, an element of traffic.